Pemanfaatan Limbah Cangkang Telur Bebek sebagai Adsorben Asam Lemak Bebas dan Katalis Heterogen CaO untuk Transesterifikasi Biodiesel dari Minyak Jelantah - Fithry, Dwi Annisa; Junaidi, Junaidi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
As an adsorbent to reduce FFA levels and as a source of Calcium Oxide (CaO) for heterogeneous catalysts. Eggshells were calcined at 900°C for 4 hours to convert CaCO3 into active CaO, which was confirmed through XRD characterization with high crystallinity. The synthesis process was carried out in two stages: adsorption pretreatment and transesterification. The results showed that the adsorption process was able to significantly reduce the FFA content of used cooking oil from 4.5% to 0.8%. Optimum transesterification conditions were achieved at an oil:methanol molar ratio of 5:1, a catalyst weight of 3% (w/w), a temperature of 60°C, and a reaction time of 2 hours, resulting in a biodiesel yield of 92.4%. The physicochemical characteristics of the biodiesel produced include: density of 870 kg/m³, kinematic viscosity of 4.3 cSt, acid number of 0.42 mg-KOH/g, iodine number of 54 g-I2/100g, saponification number of 165.495 mg-KOH/g, and cetane number of 53. All test parameters have met the quality standard of SNI 7182:2015, indicating that duck eggshell waste has great potential as an economical and environmentally friendly catalyst raw material.